The Effectiveness of Using Word Adventure Game in Improving Students’ English Vocabulary Mastery in Fifth-Grade at MI Hidayatussibyan Lancar - Novi Nur Hidayati; Zulfa Nabila (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Students often face difficulties mastering English vocabulary due to conventional rote memorization and passive learning, a problem also observed among fifth-graders at MI Hidayatussibyan Lancar. This study aims to investigate the effectiveness of using the Word Adventure Game in improving students' English vocabulary mastery. Utilizing a quantitative approach with a quasi-experimental non-equivalent pretest-posttest control group design, two intact classes were selected via purposive sampling: an experimental group taught using the game and a control group taught through conventional methods. The research instrument was a validated vocabulary mastery test based on the topic "A Lot of Stories," with data analyzed via the Independent Samples t-test. The results showed a significant improvement in the experimental class's mean score, rising from 56.25 to 85.00, compared to the control group's increase from 53.33 to 71.11. Statistical analysis confirmed a significant difference (p = 0.001 < 0.05). In conclusion, the Word Adventure Game is an effective instructional strategy that provides an interactive, collaborative, and meaningful learning environment, successfully enhancing young learners' vocabulary acquisition.